Cryotherapy reinvented: Application of phase change material for recovery in elite soccer - Clifford, T.; Abbott, W.; Kwiecien, S. Y.; Howatson, G.; McHugh, M. P. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine whether donning lower-body garments fitted with cooled phase change material (PCM) would enhance recovery after a soccer match. Methods: In a randomized, crossover design, 11 elite soccer players from the reserve squad of a team in the second-highest league in England wore PCM cooled to 15°C (PCMcold) or left at ambient temperature (PCMamb; sham control) for 3 h after a soccer match. To assess recovery, countermovement jump height, maximal isometric voluntary contraction (MIVC), muscle soreness, and the adapted Brief Assessment of Mood Questionnaire (BAM+) were measured before 12, 36, and 60 h after each match. A belief questionnaire was completed preintervention and postintervention to determine the perceived effectiveness of each garment. Results: Results are comparisons between the 2 conditions at each time point postmatch. MIVC at 36 h postmatch was greater with PCMcold versus PCMwarm (P=.01; ES=1.59; 95% CI, 3.9-17.1%). MIVC also tended to be higher at 60 h postmatch (P=.05; ES=0.85; 95% CI, -0.4% to 11.1%). Muscle soreness was 26.5% lower in PCMcold versus PCMwarm at 36 h (P=.02; ES=1.7; 95% CI, -50.4 to -16.1 mm) and 24.3% lower at 60 h (P=.04; ES=1.1; 95% CI, -26.9 to -0.874 mm). There were no between-conditions differences in postmatch countermovement jump height or BAM+ (P>.05). The belief questionnaire revealed that players felt the PCMcold was more effective than the PCMamb after the intervention (P=.004). Conclusions: PCM cooling garments provide a practical means of delivering prolonged postexercise cooling and thereby accelerate recovery in elite soccer players.